2014
DOI: 10.1109/tmtt.2014.2349873
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty of Radiometer Calibration Loads and Its Impact on Radiometric Measurements

Abstract: We present an uncertainty analysis of radiometer calibration. The procedure can be used to determine the uncertainty in the nominal brightness temperature of the unknown scene. A total power radiometer requires frequent calibration with known reference loads that are connected to the radiometer. Our analysis includes uncertainties from the radiometer calibration loads and from the connecting network (CN) that is required to multiplex calibration loads and scene to the radiometer input. We show the design and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…LN2cals of the HATPRO‐G4 are mainly affected by three error sources: (i) the uncertainty of the refractive index of liquid nitrogen; (ii) nonzero reflectance of the radiometer's horn antenna; and (iii) the entrainment of oxygen into the bath [ Maschwitz et al , ; Pospichal et al , ; Paine et al , ]. Kaisti et al [] showed that the increase of the LN2 boiling point due to hydrostatic pressure is smaller than 0.05 K for filling heights of the cryogenic load of a few centimeters (maximum 7 cm above the target) as used in our measurement setup.…”
Section: Performance Of Calibration Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…LN2cals of the HATPRO‐G4 are mainly affected by three error sources: (i) the uncertainty of the refractive index of liquid nitrogen; (ii) nonzero reflectance of the radiometer's horn antenna; and (iii) the entrainment of oxygen into the bath [ Maschwitz et al , ; Pospichal et al , ; Paine et al , ]. Kaisti et al [] showed that the increase of the LN2 boiling point due to hydrostatic pressure is smaller than 0.05 K for filling heights of the cryogenic load of a few centimeters (maximum 7 cm above the target) as used in our measurement setup.…”
Section: Performance Of Calibration Techniquesmentioning
confidence: 99%
“…In addition to the resonant effect, Paine et al [] found that LN2cals are affected by the entrainment of oxygen into the liquid nitrogen bath inducing an increase of the cold reference's temperature up to 0.4 K during a LN2cal, depending on wind conditions and the length of the calibration activity. Kaisti et al [], who combined models and observation, estimated the accuracy of the cryogenic target to be ±1.25 K.…”
Section: Introductionmentioning
confidence: 99%
“…These loads are connected to the radiometer through a lossy connecting network. We describe the uncertainty and stability of these loads and the effect of the connecting network in [6]. In the measurements and in the example simulation presented in this paper the scene is a matched load (ML) inside a temperature stabilized radiometer box with a set brightness temperature of T ML = 300.15 K.…”
Section: Instrumentationmentioning
confidence: 99%
“…The solved scene is then also given at the calibration plane from where it needs to be converted to the scene terminals. We describe these conversions in [6] and here we only consider the analysis at the calibration plane.…”
Section: Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation